THE ETHICAL RELATIONSHIPS OF PEOPLE AND PLACE: Theoretical Analysis on Muslim Communities Environmental Responsibility - Pratisti, Siti Aliyuna (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
This article discusses theoretical analysis of environmental responsibility based on Muslim communities’ perspectives. By exploring variety of theoretical standpoint, from Muslim environmentalism, relations of religion and place, to discussion on environmental responsibility, this article aims to construct a clear theoretical framework of Muslim communities’ environmental responsibility in dealing with environmental crisis. With focusing on Muslim environmental movements in Indonesia, this article employs rich textual study on Islamic environmental ethics also non-monolithic Muslim community experiences. Finding shows that moral imaginaries of sustainable community in Islam provide an expression for Muslim to engage in environmental movement. However, for Muslim, this expression is highly dependent on the experiences, cultural interpretations, and social bonding that contribute significantly in shaping community perception of environmental responsibility. Without exploring the multidimensional factors, indicating Muslim environmental responsibility is a highly difficult task to do. Keywords: Environmental responsibility, Islamic environmental ethics, Place-based narrative